APLIKASI PREDIKSI HARGA AYAM DENGAN METODE NAIVES BAYES PADA SUPPLIER AYAM POTONG - Renaldy -; Dicky Surya Dwi Putra (ALGOR, 2023)
In this modern era, everything cannot be separated from the help of data innovation and innovation, which is now also far developed than before so that many people use it in their daily routines, as well as many business visionaries who use data innovation. and stay up to date with all rounds of events. time that finally pushed work on his business. In this review, I take the issue of the visionaries of the chicken business where the problem they face is in determining the selling price of chicken, sometimes they can't determine the right selling price for the chicken, thus making them experience extensive experience. misfortune, therefore I explored to create an application that can be used by visionaries of the roast chicken business in determining the selling price of chicken. The technique I use in this examination is the Naives Bayes strategy. In addition, the testing technique used is the BlackBox Testing and Questionnaire strategies. This application is expected to make it easier for visionaries of the chicken business to determine the selling price of chicken.